Saliva could act as an emulsifier during oral processing of oil/fat. Issue 1 (14th November 2018) - Glumac, Miodrag; Qin, Lanxi; Chen, Jianshe; Ritzoulis, Christos
Abstract: Human saliva is a fluid naturally secreted in the oral cavity that interacts with food and food components for bolus formation, structure degradation, as well as lubrication. Because of the presence of salivary proteins, we speculate that saliva could also function as an effective emulsifier during oral processing of oil/fat. In this preliminary work, experiments were then designed to test this hypothesis. Whole human saliva from three healthy subjects were collected and analyzed for protein content, surface tension, and molecular weight distribution. Saliva emulsions were obtained both in vitro one and in situ for all three participating subjects. Droplet size distribution, zeta potential, and microstructure of such emulsions were examined immediately after the emulsification. Results show that stable saliva emulsions can be produced during oral processing of either pure oil (rapeseed oil) or fat food (pork belly in this work). Sodium dodecyl sulfate–polyacrylamide gel electrophoresis (SDS‐PAGE) analysis showed that protein fractions of 27 and 55 kDa molecular weights were favored for emulsion formation. This work suggests that human saliva could function as an effective emulsifier and oral emulsification could be an important mechanism for the oral processing of oil/fat. Despite being preliminary, findings from this work provide a new scientific insight to our understanding of the oral behavior of oil/fat and their sensory perception. Practical applications: Food industry is currently under a growing pressure to use novel techniques and ingredients to minimize the use of oil/fat in food products but without compromising its sensory quality. However, food industry has limited progresses because of the lack of understanding of the mechanisms of oral sensation and perception of oil/fat. Whereas there have been extensive debates about the sensory mechanisms of oil/fat, this work takes a step back by examining the oral behavior of oil/fat. Findings show that saliva can actually function as emulsifier to oil/fat, which means that ingested oil/fat will be dispersed and converted into an emulsion at the oral stage. The findings from this work offer food industry new insight on the sensory mechanisms of oil/fat.